The Vibrational Analysis of Pyridoxine and its H2O Clusters By Ab-Initio Density Functional Method - Bülbül, Berna Atak; Akü, Sevim (Yıldız Technical Univ, Yıldız Campus, Beşiktaş, İstanbul, 34349, Turkey, 2015)
The conformations of pyridoxine were searched by means of torsion potential energy surfaces scan studies through dihedral angles D1 (9H-8O-4C-3C), D2 (12H-10C-5C-6N), D3 (15O-14C-2C-1C) and D4 (O22-19H-3C-2C). In all calculations, Ab-Initio DFT ( Density Functional Theory) method used and 6311G++(d,p) basis set has been chosen. The molecular geometries of pyridoxine and pyridoxine-H2O complexes were optimized using DFT method at 6-311++G(d,p) level of theory. The harmonic and anharmonic vibrational wavenumbers, IR and Raman intensities of the most stable monomer was calculated. The results were compared with the experimental data. The assignment of the vibrational modes were determined by using GAR2PED program. HOMO-LUMO energy gap was calculated.
Keywords: Ab Initio Calculations; DFT; H2O cluster; Pyridoxine; Vibrational Spectra; Vitamin B-6